Could the members of the 1897 Andrée balloon expedition have survived? - Lantz, Björn (Polar Record, 2018)
After making a final landing with their hydrogen balloon on the Arctic pack ice on 14 July 1897 at 82°56’N 29°52’E, expedition members Salomon August Andrée, Nils Strindberg and Knut Frænkel began a slow march with very heavily laden sledges over the ice in order to try to reach a depot at Cape Flora. Two fundamental errors regarding where to go and what to bring sealed their fate. This note will explore the theory that, given the information they had at the time, the explorers should not have made these mistakes. In fact, the expedition members could have survived if they had instead travelled directly to their other depot at Seven Islands with more lightly laden sledges